The Recovery of Paul's Female Colleagues in Nineteenth-Century Feminist Biblical Interpretation - Marshall, Jill E. 1981- (2017)
In the nineteenth century, women did not gain admission to universities to study biblical languages and the new “higher criticism.” This does not mean, however, that women did not undertake critical, scholarly interpretation of the Bible. This essay examines how two late nineteenth-century American authors—Harriett Beecher Stowe and Ellen Battelle Dietrick—challenged church- and academy-based interpretation of Paul's female colleagues, Lydia, Prisca, and Phoebe. Through their own ideological lenses influenced by the church, American culture, and women's rights movements, they each engaged academic arguments and critiqued the gendered biases that shaped how male scholars and clerics interpreted primary sources and created arguments about biblical women.